Multi-Shuttle Automated Storage and Retrieval System - Mostofi, Amirhossein; Erfanian, Hamidreza (Review of Industrial Engineering Letters, 2018)
Automated Storage and Retrieval Systems (AS/RS) are being widely used in the logistics industry. This typical System, Systems are computer controlled storage systems that can automatically store and retrieve loads. Major advantages of AS/RS include high throughput, efficient use of space, high reliability and improvement of safety. There are some different operational modes in typical system. The choice of operational mode depends on the storage location assignment policy. Shared storage approach is one of these policies. In this approach, the empty space created by an act of accumulation throughout recovery can be quickly filled which conduces to save time and money. This paper examines the joint optimization of (AS/RSs) scheduling in multi-shuttle AS/RSs under shared storage in fuzzy and dynamic environment. From the view of analytical model, the advantage of operational mode under shared storage is verified. For optimization multi-shuttle automated storage and retrieval system to minimize travel time, present a zero-one fuzzy mathematical programming model. Use Genetic algorithm (GA) with Matlab software to solve large-sized problems. Various numerical experiments are conducted to evaluate the performance of the proposed algorithm and investigate the impact of different parameters on computational efficiency. The result indicates that in matters where the primary objective is to reduce travel time cycle, shared storage policy is appropriate. Furthermore, the fuzzy sets theory can be an effective tool to model the uncertainties which are available around the real applications.